Seher Shah: The lightness of Mass - Jhaveri, Shanay; Shah, Seher; Vali, Murtaza (Dubai; Green. Art. Gallery, Alserkal Avenue, 2016)
Exhibition catalog. Texts by Shanay Jhaveri, Murtaza Vali. Photographs by Randhir Singh.
English
Keywords: N4390-5098 Visual Arts- Exhibitions